On the kinematic design of anthropomorphic lower limb exoskeletons and their matching movement. (27th September 2019) - Ren, Bin; Liu, Jianwei; Luo, Xurong; Chen, Jiayu
The lower limb exoskeleton is a wearable device for assisting medical rehabilitation. A classical lower limb exoskeleton structures cannot precisely match the kinematics of the wearer's limbs and joints in movement, so a novel anthropomorphic lower limb exoskeleton based on series–parallel mechanism is proposed in this article. Then, the human lower limb movements are measured by an optical gait capture system. Comparing the simulation results of the series–parallel mechanism with the measured human data, the kinematics matching model at the hip joint is established. The results show that the kinematic matching errors in the X, Y, and Z directions are less than 2 mm. So, the proposed kinematics matching model is effective and the anthropomorphic series–parallel mechanism has a significant improvement in tracing the human positions at the hip joint.